Evolution of Broadband Intelligent Speedup Platform to SDN Architecture - Yuyong Jia; Bo Yuan; Xiaoying Huang (Dianxin kexue)
SDN is a new network architecture, which achieves the flexible control of network traffic by separating the network device control plane and data forwarding plane. Broadband intelligent speedup platform was put forward by China Telecom which followed PCC/RACF architecture, and it was the core cell of the intelligent pipeline strategy to be in charge of the policy control. The similarities and differences between SDN architecture and broadband intelligent speedup architecture were analyzed, and in view of the shortcomings of the broadband intelligent speedup platform, the feasible evolution of broadband intelligent speedup platform based on SDN was put forward.